THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE (CASE STUDY: DINAS KESEHATAN MANADO) - Mottoh, Stevani (Sam Ratulangi University, 2015)
ABSTRACT Â Employee performance is an important thing in a company or organization. It plays a vital role because performance of the company or organization depends on their employee performance. There are many factors that influence the performance such as leadership style. The objective of this research is to know the influence of transformational and transactional leadership style on employee performance. This research use casual type of research where it will investigate the influence of transformational leadership and transactional leadership style on employee performance. 30 employees of Dinas Kesehatan Manado (DINKES) were surveyed as respondents. This study reveals that Transactional leadership style has not significant effect partially on employee performance and Transformational leadership style has significant effect partially on employee performance in DINKES Manado. Therefore, to increase employee performance in DINKES Manado these two factors should be considered intensively. Keywords : Employee Performance, Transformational leadership, Transactional leadership